MULTIGRADE TEACHING: UPAYA MENGATASI MASALAH PENDISTRIBUSIAN GURU YANG TIDAK MERATA DI INDONESIA - Hendikawati, Putriaji (Universitas Negeri Semarang, 2008)
One of classic educationÃ¢â¬Ës problem in Indonesia is the teacher distribution is notspread evenly. This problem that happened mainly at isolated area, had emphasizedteacher to teach more than one lesson, moreover to teach more than one class. Thiskind of teaching called multi grade teaching (MGT) or it was known as multi classteaching in Indonesia. The characteristic of this teaching identified when teacherteached two or more different class grade in the same room, also in the same time.MGT can be applied for the several reasons, such as geography position is difficult tobe reached, limition of class room, lack of teacher, small number of student, the absentof teacher, or maybe because of the safety factor and emergency situation that happenlike on evacuation area that impacted by disaster. The development of this modelneeds to be handled careful, starts from curriculum development and also materialdevelopment, therefore advice, examine and deep perfection by education expert stillneed to be done continuously.Kata kunci: multigrade teaching, pendistribusian, guru, tidak merata.